2017
DOI: 10.1177/1352458517704078
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a home-based palliative approach for people with severe multiple sclerosis

Abstract: Background:Evidence on the efficacy of palliative care in persons with severe multiple sclerosis (MS) is scarce.Objective:To assess the efficacy of a home-based palliative approach (HPA) for adults with severe MS and their carers.Methods:Adults with severe MS-carer dyads were assigned (2:1 ratio) to either HPA or usual care (UC). At each center, a multi-professional team delivered the 6-month intervention. A blind examiner assessed dyads at baseline, 3 months, and 6 months. Primary outcome measures were Pallia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 34 publications
0
88
0
1
Order By: Relevance
“…In the PeNSAMI RCT, the HPA teams identified the pre-specified care needs (11 pre-set categories forming three domains, namely “managing everyday life”, “organization”, “psychosocial”) and those which were/were not fulfilled at the end of the intervention [ 11 ]. While these three macro areas were also detected in the present qualitative study, the overlap between the sub-categories of needs and their fulfilment is not complete in the two sets of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PeNSAMI RCT, the HPA teams identified the pre-specified care needs (11 pre-set categories forming three domains, namely “managing everyday life”, “organization”, “psychosocial”) and those which were/were not fulfilled at the end of the intervention [ 11 ]. While these three macro areas were also detected in the present qualitative study, the overlap between the sub-categories of needs and their fulfilment is not complete in the two sets of data.…”
Section: Discussionmentioning
confidence: 99%
“…The PeNSAMI (Palliative Network for Severely Affected Adults with Multiple Sclerosis in Italy) trial, the most recently published study, was a two-arm parallel, examiner-blind RCT that assessed a home palliative approach (HPA) in 50 patient-caregiver dyads versus usual care in 26 dyads. Participant characteristics and the intervention are summarized in S1 Appendix ; the full trial protocol and results are reported elsewhere [ 10 , 11 ]. Although the PeNSAMI intervention was carefully planned with the direct participation of key stakeholders [ 6 ], it was less effective than anticipated: while symptom burden was reduced, the reduction was later than expected, and changes in QOL and other patient and caregiver outcomes did not differ compared to usual care [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Turin in Italy considered a broader group of neurological diseases-MND/ALS, MS, PD and Parkinson's plus disorders-and showed that the involvement of the wider multidisciplinary palliative care team led to improvement in symptoms-pain, breathlessness, sleep disturbance and bowel symptomsand quality of life, but no significant changes in caregiver burden (29). However an Italian study on short term input in MS showed the involvement of specialist nurses, who had received extra training in palliative care and support, did lead to a reduced symptom burden but had no effect on quality of life or other outcomes (30).…”
Section: Neurologymentioning
confidence: 99%
“…COI studies are often carried out together with costutility analyses and Quality of Life Surveys (60,61). The focus of the literature is on new therapeutic options as well as the progressive forms of the disease; some research projects concerning palliative approaches to severe MS or communication in SP MS are being carried out (62).…”
Section: % Of Patientsmentioning
confidence: 99%